PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG MELAKUKAN RIGHT ISSUE PADA TAHUN 2016 - Tengku Irahmah; Emrinaldi Nur DP; Azwir Nasir (PEKBIS, 2020)
The objectives of this study was to analyze the Influence Of Mechanism Of GoodCorporate Governance (proxied as Independent Commissioners, InstitusionalOwnership, Blockholder Ownership, Audit Committee) and Capital Structure(proxied : DER) On Firm Value and mediated by Earnings Management onCompanies that right issue and companies listed in Indonesia Stock Exchange forthe periode 2016. The population in this study is on Companies that right issue andcompanies listed in Indonesia Stock Exchange for the periode 2016. The sampleswere 35 companies taken by using purposive sampling technique. Path Analysismodel was developed to test the hypotheses with the help of software SPSS version19.0. The results of the study showed that Independent Commissioners, InstitusionalOwnership, Blockholder Ownership had positive significant influence on the value ofcompanies listed in the Indonesia Stock Exchange on the right issue companies.Earning Management had negative significant on the firm value. Partially, Auditcommittee and capital structure not have any significant influence on firm value.Based on the result, Earning management acted as intervening variable ofIndependent Commissioners, Institusional Ownership and Blockholder Ownership.